Changing Canada: Political Economy as Transformation - Clement, Wallace; Vosko, Leah F. (McGill-Queen's University Press, 2003)
Changing Canada examines political transformations, welfare state restructuring, international boundaries and contexts, the new urban experience, and creative resistance. The authors question dominant ways of thinking and promote alternative ways of understanding and explaining Canadian society and politics that encourage progressive social change. They examine how the evolution of capitalism is producing new types of transformations and new forms of resistance, and show that aspects of the state and the wider society are being contested. They also discuss the often paradoxical or contradictory effects of various social forces, such as the liberating but also constraining features of new communications technologies, new employment norms, and new household forms. –Publisher's description
Available at Internet Archive to readers with print disabilities: https://archive.org/details/changingcanadapo0000unse OCLC: 50843884
Keywords: Aufsatzsammlung; Canada; Canada Conditions sociales 1991-; Canada Conditions économiques 1991-; Canada Economic conditions 1991-; Canada Politics and government 1980-; Canada Politics and government 1993-2006; Canada Politique et gouvernement 1993-2006; Canada Social conditions 1991-; Capitalisme; Changement politique; Changement social; Changement économique; Développement social Canada; Economic history; Kanada; Politics and government; Politieke ontwikkeling; Politische Ökonomie; Politischer Wandel; Science économique; Since 1980; Sociaal-economische ontwikkeling; Social change; Social change Canada; Social conditions; Sozialer Wandel; Wirtschaftsreform; État-Providence

Narratives at Work: Women, Men, Unionization, and the Fashioning of Identities - Cullum, Linda K (Memorial University Press, Institute of Social and Economic Research, 2003)
In February, 1948, a group of fish and blueberry processors formed the exclusively female, Ladies' Cold Storage Workers Union at Job Brothers fish plant in St. John's, Newfoundland. Unusual for the time, this organization was founded in the context of structural and social change in the Newfoundland fishery that altered the social relations of paid and unpaid work for women fish plant labourers. Cullum carefully explores this specific labour process and provides an open reading of the workers' narratives; a study of how the women of Job Brothers recounted stories of their work and domestic lives, and thus fashioned shifting identities as gendered, classed, and racialized subjects. –Publisher's description
OCLC: 757391847

Trade Unions in Renewal: A Comparative Study - Fairbrother, Peter; Yates, Charlotte A. B. (Charlotte Alyce Bronwen) (Continuum, 2003)
This comprehensive survey of continuity and change in trade unions looks at five primarily English-speaking countries: the USA, Canada, Australia, New Zealand and the UK. The authors consider the recent re-examination by trade union movements of the basis of union organization and activity in the face of a harsher economic and political climate. One of the impetuses for this re-examination has been the recent history of unions in the USA. American models of renewal have inspired Australia, New Zealand and the UK, while Canada has undergone a cautious examination of the US model with an attempt to develop a distinctive approach. This book aims to provide a thorough grounding for informed discussion and debate about the position and place of trade unions in modern economies. –Publisher's description
Available at Internet Archive to readers with print disabilities: https://archive.org/details/tradeunionsinren0000unse/mode/2up
Keywords: Commonwealth countries. Comparative industrial relations. Syndicats. Relations industrielles comparées. Sindicalismo. Sindicato. Comparative industrial relations. Labor unions; Labor unions. Labor unions; United States. Labor unions

Michel Chartrand : la colère du juste, 1968-2003 - Foisy, Fernand (Lanctôt, 2003)
Deuxième volet de la biographie de Michel Chartrand (Les voix d’un homme de parole), La colère du juste retrace les événements marquants de la vie du célèbre syndicaliste depuis mai 1968 jusqu’à nos jours. Ses prises de position éclatantes, ses multiples démêlées avec l’appareil judicaire, ses nombreux emprisonnements, dont sa détention lors de la crise d’Octobre 1970 (« Un jour quelqu’un va payer pour tous ces jours passés sans soleil et sans femme… »), les luttes multiples, syndicales et autres, qu’il a menées pour le mieux-être et la sécurité des travailleurs, les complots et manigances douteuses dont il a été souvent victime, avec en toile de fond une tranche importante de l’histoire du Québec moderne, tels sont les principaux éléments qui forment la trame de cette biographie imposante. Fernand Foisy a réussi à recréer le climat de l’époque, en donnant la parole aux principaux acteurs, rectifiant ici et là certaines notions erronées qui ont été véhiculées à propos de ce indomptable justicier au tempérament fougueux, Michel Chartrand. Un homme d’action et de parole, dont on découvrira tout le charme et ses passions pour la culture. Ce deuxième tome coïncide avec la diffusion de la deuxième partie de la série Simone et Chartrand, diffusée cet automne sur les ondes de Télé-Québec. –Résumé de l'éditeur
https://classiques.uqam.ca/contemporains/foisy_fernand/michel_chartrand_colere/michel_chartrand_colere.html OCLC: 54817836
Keywords: Biographies; Chartrand; Michel; Dirigeants syndicaux Québec (Province) Biographies; History; Labor leaders; Labor leaders Québec (Province) Biography; Labor unions; Labor unions Québec (Province) History; Politics and government; Québec; Québec (Province) Conditions sociales 1960-1991; Québec (Province) Politics and government 1960-; Québec (Province) Politique et gouvernement 1960-; Since 1960; Syndicalism; Syndicalism Québec (Province); Syndicalisme Québec (Province); Syndicats Québec (Province) Histoire; Travailleurs Québec (Province) Conditions sociales; Travailleurs Québec (Province) Histoire; Working class; Working class Québec (Province) History; Working class Québec (Province) Social conditions; Working class Social conditions

L'histoire des mineurs du nord ontarien et québécois, 1886-1945 - Gaudreau, Guy; Daoust, Alain; De la Riva, Paul; Reilly, Karey (Septentrion, 2003)
L’auteur fait revivre les itinéraires de milliers de travailleurs qui ont sillonné les mines du Nord-Est ontarien et du Nord-Ouest québécois au cours des premières décennies du xxe siècle. Grâce à l’exploitation des dossiers du personnel de sept sociétés minières réparties sur ce territoire, il scrute les arrivées et les départs des ouvriers-mineurs en cherchant à comprendre leurs motivations. L’image se dégageant de ces sources patronales reste fort différente de celle rapportée par l’histoire ouvrière et syndicale. En effet, ces travailleurs quittent d’eux-mêmes leur emploi beaucoup plus souvent qu’ils ne sont congédiés ou mis à pied, de sorte que leur chômage serait davantage volontaire qu’imposé. Étant donné la relative rareté de la main-d’œuvre spécialisée, les employeurs n’auraient pas eu d’autre choix que de réembaucher ceux qu’ils avaient auparavant engagés, et même ceux qu’ils avaient déjà congédiés. En somme, ces travailleurs, qui annoncent très souvent leur décision de « sacrer leur camp », affichent une indépendance face aux entreprises et une capacité de résistance qu’on ne soupçonnait pas. –Résumé de l'éditeur
OCLC: 54826122
Keywords: History; Mineral industries; Mineral industries Ontario; Northern History; Mineral industries Québec (Province) Abitibi-Témiscamingue History; Miners; Miners Ontario; Northern History; Miners Québec (Province) Abitibi-Témiscamingue History; Mineurs Québec (Province) Abitibi-Témiscamingue Histoire; Northern Ontario; Québec Abitibi-Témiscamingue

Westcountrymen in Prince Edward's Isle - Greenhill, Basil; Giffard, Ann (Formac, 2003)
This classic, first-of-its-kind study of merchant shipping illuminates the manner in which the rapid development of shipbuilding in Prince Edward Island played a significant role in Canada's early history. James Yeo, Sr., once a village labourer in his native Cornwall, came to the colony and quickly amassed a fortune from both shipbuilding and trade. His rough-and-ready business deals spawned his mercurial rise to prominence in the colony. First published in 1967, this book originated from an idea by Ann Giffard and was jointly executed with her husband, Basil Greenhill. It connects the burgeoning expansion of shipbuilding in the colonies with the settlers' hometown in Devon, and explains why, when Britain was cut off from supplies of wood in Europe, shipbuilding suddenly took hold in Canada. It is an unique study that shows that local history is an important window into the interconnected world of economic development. –Publisher's description
Table of contents: http://catdir.loc.gov/catdir/toc/fy0601/2003495912.html
Keywords: Commerce; Great Britain; Great Britain Commerce Prince Edward Island; History; Prince Edward Island; Prince Edward Island Commerce Great Britain; Shipbuilding; Shipbuilding Prince Edward Island History; Shipping; Shipping Prince Edward Island History

Industrial Sunset: The Making of North America's Rust Belt, 1969-1984 - High, Steven C. (University of Toronto Press, 2003)
Plant shutdowns in Canada and the United States from 1969 to 1984 led to an ongoing and ravaging industrial decline of the Great Lakes Region. This book offers a comparative regional analysis of the economic and cultural devastation caused by the shutdowns, and provides an insightful examination of how mill and factory workers on both sides of the border made sense of their own displacement. The history of deindustrialization rendered in cultural terms reveals the importance of community and national identifications in how North Americans responded to the problem. Based on the plant shutdown stories told by over 130 industrial workers, and drawing on extensive archival and published sources, and songs and poetry from the time period covered, Steve High explores the central issues in the history and contemporary politics of plant closings. In so doing, this study poses new questions about group identification and solidarity in the face of often dramatic industrial transformation. –Publisher's description
Book available at Internet Archive to readers with print disabilities: https://archive.org/details/industrialsunset0000high

When Coal was King: Ladysmith and the Coal-Mining Industry on Vancouver Island - Hinde, John Roderick (UBC Press, 2003)
The town of Ladysmith was one of the most important coal-mining communities on Vancouver Island during the early twentieth century. The Ladysmith miners had a reputation for radicalism and militancy and engaged in bitter struggles for union recognition and economic justice, most notably the Great Strike of 1912-14. This strike, one of the longest and most violent labour disputes in Canadian history, marked a watershed in the history of the town and the coal industry. –Publisher's description
Book available at Internet Archive to people with print disabilities: https://archive.org/details/whencoalwaskingl0000hind
Keywords: British Columbia Ladysmith; British Columbia Vancouver Island; Coal miners; Coal mines and mining; Coal mining History; History; Ladysmith (B.C.); Social aspects History; Social conditions History; Strikes and lockouts

From Consent to Coercion: The Assault on Trade Union Freedoms - Panitch, Leo; Swartz, Donald (Garamond Press, 2003)
Examines the "coercive assault" (i.e., legislative overrides) on trade union rights in Canada by both federal and provincial governments from the 1970s to the early 2000s. Also discusses labour-related decisions of the Supreme Court, and strategies for union renewal. Includes tables of union membership, strikes and lockouts, back-to-work measures, use of designations, and complaints of violations of union rights filed with the International Labor Organization.
Keywords: Collective bargaining; History; Labor Unions; Law and legislation

Gendered States: Women, Unemployment Insurance, and the Political Economy of the Welfare State in Canada, 1945-1997 - Porter, Ann (University of Toronto Press, 2003)
In the period since the Second World War there has been both a massive influx of women into the Canadian job market and substantive changes to the welfare state as early expansion gave way, by the 1970s, to a prolonged period of retrenchment and restructuring. Through a detailed historical account of the Unemployment Insurance (UI) program from 1945 to 1997, Ann Porter demonstrates how gender was central both to the construction of the post-war welfare state, as well as to its subsequent crisis and restructuring. Drawing on a wide range of sources (including archival material, UI administrative tribunal decisions, and documents from the government, labour and women's groups) she examines the implications of restructuring for women's equality, as well as how women's groups, labour and the state interacted in efforts to shape the policy agenda. Porter argues that, while the post-war welfare state model was based on a family with a single male breadwinner, the new model is one that assumes multiple family earners and encourages employability for both men and women. The result has been greater formal equality for women, but at the same time the restructuring and reduction of benefits have undermined these gains and made women's lives increasingly difficult. Using concepts from political economy, feminism, and public policy, this study will be of interest across a range of disciplines. –Publisher's description
Keywords: Economic policy; Employment; History; Social policy; Unemployment insurance; Women

Paul has a Summer Job: Graphic Novel - Rabagliati, Michel. (Drawn and Quarterly, 2003)
Rabagliati's strip "Paul: Apprentice Typographer" was one of the highlights of 1999's Drawn & Quarterly anthology, and his first comic book Paul in the Country won the 2000 Harvey award for Best New Talent. This, his first graphic novel, is eagerly anticipated by comix connoisseurs who enjoy a sweet, unsentimental story about being a teenager and Rabagliati's crisp retro-modern 1950s drawing style. This book continues the story of Paul, a Quebecois teenager in the 1970s, as he experiences the first conflicts of responsibility with his desire to be free. Paul is outraged that he is forced to stop his high school art training. But he's been asked to put art aside because his other grades are so terribly low. Defiant, he quits school and anticipates a summer of leisure. But instead Paul follows the path of so many Quebecois teenagers: he lands a job as a counselor at one of the many summer camps in the mountains outside the city. There he finds himself guiding a motley band of kids, misfits and troublemakers, much like himself. After quitting school and trying his luck in the "real world," average teenager Paul gets a job as a counselor at a summer camp run for underprivileged children in 1970s Quebec. –Publisher's description
Keywords: Blue-collar work; Camp Counsellor; Comic books; strips; etc; Factory; Montreal; Quebec; Teenager

Unions in the Time of Revolution: Government Restructuring in Alberta and Ontario - Reshef, Yonatan; Rastin, Sandra (University of Toronto Press, 2003)
The election of neo-conservative governments in Alberta and Ontario in the early 1990s brought dramatic changes to provincial public policy; both the Ralph Klein Revolution and Mike Harris' Common Sense Revolution emphasized fundamental changes in the role of government, balanced budgets, and the elimination of provincial debts. While public sector unions were forced to react, the response of the Alberta and Ontario unions differed significantly. The reasons, outcome, and long-term impact of the difference is the focus of Yonatan Reshef and Sandra Rastin's careful and revealing analysis. The authors' argument concentrates on union responses to the neo-conservative transformation in the two affected provinces, but the scope of the discussion expands to cover such issues as the differences between the two regimes, the damage to the Ontario labour movement dealt by the labour-oriented NDP government, the limits of inter-union cooperation, and the role of modern unions in politics. Lively and timely, Unions in the Time of Revolution places Canada's unions in the full context of the neo-conservative trend in provincial politics, and demonstrates the importance of individual union responses in times of such significant change. –Publisher's description. Contents: Alberta and Ontario: Industrial relations and their contexts – Revolutions, Canada style – Collective action conceptual framework – Revolutionizing the Civil Service: OPSEU and AUPE – Teachers: Protecting the profession, defending the union organization – Sins of commission and sins of omissions: The Ontario days of action and missed opportunities in Alberta – Sleeping with the devil: Strategic voting in the 1999 Ontario Election – Revisiting the collective action model – Additional thoughts on collective action.
https://utorontopress.com/9780802087539/unions-in-the-time-of-revolutions/
Keywords: Alberta. Employee-management relations in government; Alberta. Government employee unions; Employee-management relations in government; Ontario. Employee-management relations in government. Government employee unions; Ontario. Fonction publique; Ontario. Fonctionnaires; Ontario. Government employee unions; Relations de travail; Syndicats

The Oriental Question: Consolidating a White Man's Province, 1914-1941 - Roy, Patricia (University of British Columbia Press, 2003)
[The author] continues her study into why British Columbians – and many Canadians from outside the province – were historically so opposed to Asian immigration. Drawing on contemporary press and government reports and individual correspondence and memoirs, Roy shows how British Columbians consolidated a “white man’s province” from 1914 to 1941 by securing a virtual end to Asian immigration and placing stringent legal restrictions on Asian competition in the major industries of lumber and fishing. While its emphasis is on political action and politicians, the book also examines the popular pressure for such practices and gives some attention to the reactions of those most affected: the province’s Chinese and Japanese residents. –Publisher's description
OCLC: 53068557
Keywords: 1900-1999; British Columbia; British Columbia Emigration and immigration History 20th century; British Columbia Politics and government 20th century; British Columbia Race relations; China; China Emigration and immigration History 20th century; Chinese; Chinese British Columbia History 20th century; Chinesen; Chinois Colombie-Britannique Histoire 20e siècle; Einwanderung; Emigration and immigration; Ethnische Beziehungen; History; Immigrants; Immigrants British Columbia History 20th century; Japan; Japan Emigration and immigration History 20th century; Japanese; Japanese British Columbia History 20th century; Japonais Colombie-Britannique Histoire 20e siècle; Politics and government; Race relations

Retooling the Mind Factory: Education in a Lean State - Sears, Alan (Garamond Press, 2003)
Alan Sears examines education reform in relation to a broad process of cultural and economic change. His book makes the case that education reform is one aspect of a broad-ranging neo-liberal agenda that aims to push the market deeper into every aspect of our lives by eliminating or shrinking non-market alternatives. The author begins by showing that advocates of education reform have had to make the case that the current system is not working. This sets the ground for an examination of the so-called 'Common Sense Revolution,' a claim that drastic change was required to redesign government policies to fit a changing world. Lean production methods are a crucial component of this changing world, and broader social and cultural change is now required to consolidate the emerging order built on the spread of these methods. Education reform is designed to recast the relations of citizenship, contributing to the cultural and social change promoted through the social policy of the lean state. –Publisher's description
Keywords: Conservatism; EDUCATIONAL change; Economic aspects; Education; Education and state; Ontario

Forces of Labor: Workers' Movements and Globalization since 1870 - Silver, Beverly J. (Cambridge University Press, 2003)
Recasting labor studies in a long-term and global framework, the book draws on a major new database on world labor unrest to show how local labor movements have been related to world-scale political, economic, and social processes since the late nineteenth century. Through an in-depth empirical analysis of select global industries, the book demonstrates how the main locations of labor unrest have shifted from country to country together with shifts in the geographical location of production. It shows how the main sites of labor unrest have shifted over time together with the rise or decline of new leading sectors of capitalist development and demonstrates that labor movements have been deeply embedded (as both cause and effect) in world political dynamics. Over the history of the modern labor movement, the book isolates what is truly novel about the contemporary global crisis of labor movements. Arguing against the view that this is a terminal crisis, the book concludes by exploring the likely forms that emergent labor movements will take in the twenty-first century. –Publisher's description. Contents: Introduction – Labor movements and capital mobility – Labor movements and product cycles – Labor movements and world politics – Contemporary dynamics in world-historical perspective – Appendix A: The World Labor Group Database: conceptualization, measurement, and data collection procedures – Appendix B: Instructions for recording data from indexes – Appendix C: Country classifications.
Keywords: Automobile industry workers; Business relocation; Capitalism; Economic aspects History; Globalization; History; Labor disputes; Labor movement; Manufacturing processes; TEXTILE workers

Walking the Union Walk: Stories From the Communications, Energy, and Paperworkers Union - Swift, Jamie (Between the Lines, 2003)
Hi-tech tactics during a strike at a dockside factory in Montreal. A workplace cancer tragedy in Sarnia, Ontario. Immigrant workers sticking with their union at the chocolate factory. A struggle for pay equity in the courts and on the streets. A campaign to create jobs by cutting hours of work in B.C. An organizing drive 350 kilometres out into the frigid Atlantic. These are some of the fascinating stories told by Jamie Swift in his chronicle of the first ten eventful years of one of the most dynamic labour unions in North America. –Publisher's description
https://btlbooks.com/book/walking-the-union-walk
Keywords: Communication; Energy and Paperworkers Union of Canada; Employees; Energy industries; History; Labor Unions; Paper industry workers; Telecommunication

All Hell Can't Stop Us: The On-to-Ottawa Trek and Regina Riot - Waiser, W. A. (Bill) (Fifth House Books, 2003)
In early June 1935, one thousand relief-camp strikers clambered aboard freight trains to take their grievances to Ottawa. Their trek would end in bloodshed on the streets of Regina on 1 July 1935, later known as "The bloodiest day of the Depression." In All Hell Can't Stop Us, noted historian Bill Waiser examines the social and political background of the On-to-Ottawa Trek and Regina Riot, and provides an in-depth account of the strikers, their supporters, and their powerful adversaries. This gripping history includes many unpublished sketches and photographs. –Publisher's description
Keywords: Unemployed – Canada – History – 20th century

Naming the System: Inequality and Work in the Global Economy - Yates, Michael D. (Monthly Review Press, 2003)
The economic boom of the 1990s created huge wealth for the bosses, but benefited workers hardly at all. At the same time, the bosses were able to take the political initiative and even the moral high ground, while workers were often divided against each other. This new book by leading labor analyst Michael D. Yates seeks to explain how this happened, and what can be done about it. Essential to both tasks is "naming the system"-the system that ensures that those who do the work do not benefit from the wealth they produce. Yates draws on recent data to show that the growing inequality - globally, and within the United States - is a necessary consequence of capitalism, and not an unfortunate side-effect that can be remedied by technical measures. To defend working people against ongoing attacks-on their working conditions, their living standards, and their future and that of their children-and to challenge inequality, it is necessary to understand capitalism as a system and for labor to challenge the political dominance of capitalist interests. Naming the System examines contemporary trends in employment and unemployment, in hours of work, and in the nature of jobs. It shows how working life is being reconfigured today, and how the effects of this are masked by mainstream economic theories. It uses numerous concrete examples to relate larger theoretical issues to everyday experience of the present-day economy. And it sets out the strategic options for organized labor in the current political context, in which the U.S.-led war on terrorism threatens to eclipse the anti-globalization movement. –Publisher's description.
https://monthlyreview.org/product/naming_the_system/
Keywords: ANTI-globalization movement; Capitalism; Globalization; Income distribution; Industrial relations; Labor; Labor movement; QUALITY of work life; Unemployment